Creating market linkages through collective action - CGIAR Program on Collective Action and Property Rights (International Food Policy Research Institute, 2010)
Supplying formal markets such as multinational supermarket chains and fast food restaurants offers both higher income and improved business relations for farmers. However, accessing these markets requires higher product quality, securer supply chains, and more efficient marketing and business management. To meet these conditions and engage with these higher value markets in the long term, farmers need increased levels of bonding social capital and strengthened bridging social capital through partnerships with service providers and market chain actors.